Intratumoral TIGIT+ CD8+ T-cell infiltration determines poor prognosis and immune evasion in patients with muscle-invasive bladder cancer - Li Liu; Quan Zhou; Yifan Chen; Weijuan Zhang; Yu Xia; Ying Xiong; Yu Zhu; Zewei Wang; Han Zeng; Hongyu Zhang; Zhaopei Liu; Qiuren Huang; et al. (Journal for ImmunoTherapy of Cancer)
Background T-cell immunoglobulin and ITIM domain (TIGIT) is identified as a novel checkpoint receptor that can facilitate immune escape via mediating T-cell exhaustion in tumors. However, the clinical significance and immune contexture correlation of intratumoral TIGIT+ CD8+ T-cells remain to be further explored in muscle-invasive bladder cancer (MIBC).Methods 259 patients with MIBC from two clinical centers (Zhongshan Hospital, n=141; Shanghai Cancer Center, n=118) were analyzed to evaluate the prognostic value and immune contexture association of TIGIT+ CD8+ T-cells through immunohistochemistry. Fresh tumor tissue samples from 26 patients with MIBC were examined to discover the phenotype of this CD8 subpopulation by flow cytometry.Results High infiltration of intratumoral TIGIT+ CD8+ T-cells predicted poor overall survival (OS) and recurrence-free survival (RFS) in MIBC. For patients with stage II MIBC with low infiltration of TIGIT+ CD8+ cells, adjuvant chemotherapy (ACT) could significantly prolong their OS and RFS. Intratumoral TIGIT+ CD8+ T-cell abundance was correlated with impaired CD8+ T-cell cytotoxicity and exhibited production of immunosuppressive cytokine IL-10. Further analysis of tumor-infiltrating immune cell landscape revealed TIGIT+ CD8+ T-cells were associated with suppressive immune contexture, including Th2 cells, regulatory T-cells, mast cells and neutrophils.Conclusion Intratumoral TIGIT+ CD8+ T-cell abundance could serve as an independent prognosticator for clinical outcome and a predictive biomarker for inferior ACT responsiveness. Intratumoral TIGIT+ CD8+ T-cell abundance correlated with dampened CD8+ T-cell antitumor immunity and immunosuppressive contexture abundance, highlighting a tumor-promoting role of TIGIT+ CD8+ T-cells.